Chemotherapy-induced peripheral neuropathy: a literature review - Martin,Lelia Gonçalves Rocha (2011)
ABSTRACT Peripheral neuropathy is a common side effect in patients undergoing cancer treatment with chemotherapy. This condition can affect patients in several different ways, interfering in their activities of daily living and autonomy. The present study aimed to review the literature on chemotherapy-induced peripheral neuropathy and its treatment or other possible interventions. The findings reveal that chemotherapy-induced peripheral neuropathy is a common condition that affects patients undergoing treatment with some specific drugs. Besides, several different substances have been used to treat or control this condition, although no significant evidence could be found in these studies.